The Impact of Internal Control System on the Financial Accountability of Non-Governmental organisations in Nigeria: Evidence from the Structural Equation Modelling - Rafindadi, Abdulkadir Abdulrashid; Olanrewaju, Zakariyah Aliyu (International Review of Management and Marketing, 2019)
This study examines the impact of internal control system on financial accountability of NGOs in Nigeria. Data was collected from primary source through the administration of three hundred and fifty-two (352) questionnaires distributed to the respondents that were selected through multi-stage sampling techniques of forty-four different NGOs in North-Western Nigeria. Data retrieved from the survey were analysed using multiple regressions analysis and the PLS in bound Structural Equation Modelling technique. The findings of the study revealed how internal control system is found to be having the significant potencies of enhancing or derailing the quality of services rendered by the NGOs and has the combined effects of predicting proper accountability in NGOs, taking all factors constant. In addition to the foregoing, the study discovered how a 1% decrease in risk assessment results to 0.155 increases in proper accountability in NGOs and vice versa. Failure of government to provide NGO regulatory laws and agencies or boards as well as the inactive participation of government in generating counterpart funding, poor attitude towards strengthening and sustainability of services often times result to poor service delivery to the targeted beneficiaries. As a result of these findings, it is recommended that government should support NGO intervention actively through the provision of counterpart funding, making policies that will be impactful in strengthening the activities of NGOs. The study also discovered that NGOs need to prioritize employees’ welfare and development as they are the agents of change. Additionally, donors and funding agencies should strengthen their evaluation processes more through periodic audit and on spot assessment in a bid to strengthen financial performance reporting. Keywords: Internal control system, NGOs, proper accountability, Staff Welfare, Cross sectional models, PLS-SEM. JEL Classifications: L31, L78, I31, C42 DOI: https://doi.org/10.32479/irmm.7909